High-Dose Inhaled Nitric Oxide for the Treatment of Spontaneously Breathing Pregnant Patients With Severe Coronavirus Disease 2019 (COVID-19) Pneumonia. Issue 2 (6th August 2022) - Valsecchi, Carlo; Winterton, Dario; Safaee Fakhr, Bijan; Collier, Ai-ris Y.; Nozari, Ala; Ortoleva, Jamel; Mukerji, Shivali; Gibson, Lauren E.; Carroll, Ryan W.; Shaefi, Shahzad; Pinciroli, Riccardo; La Vita, Carolyn; et al.
Abstract : High-dose inhaled nitric oxide was associated with shorter time on supplemental oxygen and shorter intensive care unit and hospital length of stay for pregnant patients with severe coronavirus disease 2019 (COVID-19) pneumonia. Abstract : OBJECTIVE: To evaluate whether the use of inhaled nitric oxide (iNO)200 improves respiratory function. METHODS: This retrospective cohort study used data from pregnant patients hospitalized with severe bilateral coronavirus disease 2019 (COVID-19) pneumonia at four teaching hospitals between March 2020 and December 2021. Two cohorts were identified: 1) those receiving standard of care alone (SoC cohort) and 2) those receiving iNO200 for 30 minutes twice daily in addition to standard of care alone (iNO200 cohort). Inhaled nitric oxide, as a novel therapy, was offered only at one hospital. The prespecified primary outcome was days free from any oxygen supplementation at 28 days postadmission. Secondary outcomes were hospital length of stay, rate of intubation, and intensive care unit (ICU) length of stay. The multivariable-adjusted regression analyses accounted for age, body mass index, gestational age, use of steroids, remdesivir, and the study center. RESULTS: Seventy-one pregnant patients were hospitalized for severe bilateral COVID-19 pneumonia: 51 in the SoC cohort and 20 in the iNO200 cohort. Patients receiving iNO200 had more oxygen supplementation–free days (iNO200 : median [interquartile range], 24 [23–26] days vs standard of care alone: 22 [14–24] days, P =.01) compared with patients in the SoC cohort. In the multivariable-adjusted analyses, iNO200 was associated with 63.2% (95% CI 36.2–95.4%; P <.001) more days free from oxygen supplementation, 59.7% (95% CI 56.0–63.2%; P <.001) shorter ICU length of stay, and 63.6% (95% CI 55.1–70.8%; P <.001) shorter hospital length of stay. No iNO200 -related adverse events were reported. CONCLUSION: In pregnant patients with severe bilateral COVID-19 pneumonia, iNO200 was associated with a reduced need for oxygen supplementation and shorter hospital stay.